Analisis Pengaruh Faktor Internal Terhadap Profitabilitas Bank Syariah Indonesia (BSI) Periode 2013-2022 - Meisha Fatma Wijaya; Tessalonika Federova Br Simanjuntak; Arnol Prabowo Siagian; Adyanto Armando Purba; Rista Y. Lumbangaol; Tiara Posma Udur Hutapea; Ilman Ashari Siregar (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The purpose of this study was to determine the analysis of the influence of internal factors on the profitability of Bank Syariah Indonesia (BSI) for the 2013-2022 period. The internal factors used in this study are Profit Sharing Financing, Financing to Deposit Ratio (FDR), and Operational Cost per Operating Income (BOPO). While the profitability used in this study is Return On Assert (ROA). With Time Series data for the period 2013-2022 analyzed using the Error Correction Model (ECM) as a method to see the results of the analysis of the effect of the independent variables on the dependent variable. This research was initially tested using the Ordinary Least Square (OLS) method to see the long-term effect analysis and used the ECM method to see the short-term effect analysis. The results showed that in the long term Profit Sharing Financing had a negative and significant effect on ROA, FDR had a positive and significant effect on ROA, and BOPO had a negative and significant effect on ROA. Meanwhile, in the short term Profit Sharing Financing has a negative and significant effect, FDR has a positive and insignificant effect, and BOPO has a negative and significant effect.